2016
DOI: 10.1039/c5tc03481g
|View full text |Cite
|
Sign up to set email alerts
|

Transition dipole moment orientation in films of solution processed fluorescent oligomers: investigating the influence of molecular anisotropy

Abstract: The transition dipole moments of long fluorescent oligomers in a solution processed host align with the plane of the film when aggregated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Transition dipole alignment has been achieved for solution processed fluorescent materials. [12][13][14][15] However, the efficiency of OLEDS featuring fluorescent emitters is limited by the spin statistics that lead to the generation of singlet excitons (25%), and, hence, is typically less than that of devices comprised of phosphorescent or TADF-based emitters that can exploit both the singlet and triplet excitons (100%). There has been a recent report of solution processed phosphorescent OLEDs with EQEs greater than 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Transition dipole alignment has been achieved for solution processed fluorescent materials. [12][13][14][15] However, the efficiency of OLEDS featuring fluorescent emitters is limited by the spin statistics that lead to the generation of singlet excitons (25%), and, hence, is typically less than that of devices comprised of phosphorescent or TADF-based emitters that can exploit both the singlet and triplet excitons (100%). There has been a recent report of solution processed phosphorescent OLEDs with EQEs greater than 20%.…”
Section: Introductionmentioning
confidence: 99%
“…[96][97][98][99][100][101] There has been a number of publications recently focused on such polymers and in the possibility of integrating them with small molecule emitters to achieve solution-processed films with dipoles preferentially distributed parallel to the substrate. [102 -106] For example, Senes et al [104] investigated the molecular orientation of the p-phenylene vinylene oligomers (OPVn) films doped in TPBi. They reported a V H of 0.80 in OPV7: TPBi films at high dopant concentrations (10 wt-%), due to the formation of low-aspect ratio H-aggregates.…”
Section: Solution Processed Filmsmentioning
confidence: 99%
“… 16 19 High degrees of horizontal orientation have also been recently reported for light-emitting oligomers in solution processed host/guest systems. 20 22 …”
Section: Introductionmentioning
confidence: 99%
“… 24 We have previously shown that at high concentration (10 wt%) OPV6 and OPV7 are horizontally aligned in solution processed layers of 2,2′,2′′-(benzene-1,3,5-triyl)tris(1-phenyl-1 H -benzimidazole) (TPBi) as host, where they aggregate. 20 In solution-processed 20 and evaporated 25 pristine layers, TPBi is oriented randomly. By using a polymeric host such as PFO that is able to align horizontally by itself we hope to induce horizontal alignment of the OPV6 and OPV7 guests in solution-processed layers at low concentration where aggregation is absent.…”
Section: Introductionmentioning
confidence: 99%